Hukum Memakai Cadar (Studi Komparatif Terhadap Putusan Hukum Lajnah Bahtsul Masail Nahdlatul Ulama Dengan Majelis Tarjih Dan Tajdid Muhammadiyah) - Silmi Fitrotunnisa (Jurnal Penelitian Medan Agama, 2018)
Cadar is a popular problem in Indonesia that is frequently discussed. There are differences of opinion about the law using the veil, namely groups that allow their use and those who refuse to use it. This study wants to examine the law using the veil according to Nahdatul Ulama and Muhammadiyah in the use of legal arguments using the veil. This study uses a comparative or comparative method. the conclusion that was obtained was that the Lajnah Bahtsul Masail Nahdatul Ulama and Majelis Tarjih and Tajdid Muhammadiyah differed on the legal issue of wearing the veil. In addition, Nahdatul Ulama uses the qauly method, which follows the opinions of the ulema of the school obliging and not obliging to wear a veil that follows the opinions of the ulema of the school by referring to the book Maraqil Falah Syarh Nurul Idhah and Bajuri Hasyiyah Fathul Qarib, while Muhammadiyah uses the ijtihad method bayani, where ijtihad is based on the arguments interpreted by human reason based on the arguments of the Qur'an and Hadith, so that it determines that there is no text that mentions the law using the veil, then the law of wearing the veil is not mandatory.